Andean peasant family and biological reproduction, a case study in the central Andes - Saravia, Pilar (1985)
"There is no single, global strategy valid for all of society and uniformly focused on all manifestations of sex; for example, the idea that it has often been sought by different means to reduce all sex to its reproductive function, to its heterosexual and adult form and its marital legitimacy, it does not account, without a doubt, for the multiple means used in sexual politics that concerned both sexes, different ages and different social classes.